Transitioning towards more plant-based diets: sharing expert knowledge through a system lens - Blokhuis, Christa; Hofstede, Gert Jan; Ocké, Marga; de Vet, Emely (Appetite, 2024)
Transitioning towards more plant-based protein diets is essential for public and planetary health. Current research about consumption practices of protein sources provides limited insight in the multidisciplinary nature and interconnectivity of the food environment. This study aimed to collect mental models of review authors by synthesizing both their implicit and explicit system views into an overarching system view. Published reviews were used to select participants and identify variables that explain the protein transition in relation to the food environment. To overcome differences in disciplines and scale levels (e.g. individual, interpersonal, environmental), variables were organized according to the Determinants of Nutrition and Eating Framework. Eight review authors shared their mental models in an interview. Participants were asked to construct a causal loop diagram (CLD), a tool proven valuable in making one's ontology explicit to others. Implicit system views in narrative were converted into CLDs using a coding framework. The overarching system view suggests that a multitude of feedback loops sustain current consumption patterns of protein sources, for example by reinforcement through habit, availability and peer support. Several aspects require further research, such as variable relationships that were subject to disagreement and the lack of reciprocity between the physical and social elements of the food environment. In addition, knowledge gaps were exposed, including long-term behaviour and interaction of multiple variables. As a boundary object, the overarching system view can facilitate the direction of future research. The findings underscore the interconnected nature of many disparate elements within the food environment, stressing the need for holistic methods like systems thinking. These are essential in developing a systemic understanding and facilitating the transition towards more plant-based diets.